Clinical significance of ubiquilin 1 in gastric cancer. Issue 3 (January 2018) - Bao, Jingjing; Jiang, Xiaoqin; Zhu, Xiaowei; Dai, Guihong; Dou, Rongrong; Liu, Xinyun; Sheng, Haihui; Liang, Zongmin; Yu, Hong
Abstract : Abstract: Ubiquilin 1 (UBQLN1) plays an essential role in the regulation of protein degradations which is involved in the pathophysiology of neurodegenerative diseases and cancer. This study aimed to investigate the expression level of UBQLN1 in gastric cancer and evaluated the relationship between its expression and clinicopathological characteristics, as well as prognostic of patients with gastric cancer. Immunohistochemistry (IHC) was used to detect the expression levels of UBQLN1 in 179 pairs of gastric cancer and adjacent normal tissues. The UBQLN1 was significantly upregulated in gastric cancer tissue. High UBQLN1 expression was associated with high histological grade, invasion, lymph node metastasis, and tumor node metastasis (TNM) stage III ( P < . 001). Multivariate Cox analysis showed that larger tumor size (HR = 3.125, 95%CI: 2.031–4.808, P  < .001), histological grade 3 (HR = 15.313, 95%, CI: 8.075–29.041, P  < .001), pT3 + pT4 (HR = 3.224, 95%CI: 1.389–7.483, P  = .006), LNM (HR = 4.467, 95%CI: 2.404–8.302, P < . 001), TNM stage III (HR = 2.152, 95%CI: 1.289–3.594, P = . 003), and high UBQLN1 expression (HR = 2.547, 95%CI: 1.511–4.292, P < . 001) were significantly associated with worse prognosis of patients with gastric cancer. In conclusion, high UBQLN1 expression was an independent worse prognostic factor for patients with gastric cancer.